Memanfaatkan Kekuatan Media Sosial Dalam Mempromosikan Produk Tempe Disaat Pandemi Covid-19 - Devi Pitrianingsih; Ika Ratnasari; Dwy Epty Hidayati; Santi Pratiwi Hari Sandi (Journal of Management and Social Sciences, 2023)
In 2020 Indonesia is facing a pandemic situation due to the Corona Virus Disease 2019 (COVID-19) outbreak which has a deep impact on various economic sectors, especially on Micro, Small and Medium Enterprises (MSMEs). Digital marketing is currently one of the marketing strategies needed by business people in order to increase sales. Digital marketing is increasingly showing its fangs and as one of the best solutions that can be used by business people to expand their business circle. The purpose of this article is to improve the ability or skills of MSME players in marketing products through online media. This method uses a descriptive approach with observative and by identifying trends in current consumers and consumer preferences for alternative foods. The result of this article is that in the face of increasingly fierce market competition, tempeh producers need to adopt innovative marketing strategies and use social media as the main tool to promote tempeh products. The conclusion is that by utilizing the power of social media, tempeh producers can expand their market reach, strengthen their brand, and increase consumer loyalty. The implication of the industrial visit is the importance of understanding and using social media as an effective marketing tool in the food industry, especially in promoting tempeh products.